Studi Evaluasi Program Tahsin Online dalam Meningkatkan Kompetensi Membaca Al-Qur’an pada Usia Lanjut - Yandi Mariana M.B Kondakh; Mahmudin Sudin (Al-Mudarris, 2026)
This study evaluates the implementation of online tahsin programs for older adults as a form of sustainable Islamic education that supports lifelong Qur’anic learning. The research addresses the growing need for accessible Islamic educational programs for elderly learners who experience physical, cognitive, and technological limitations in conventional learning settings. This study aims to analyze the effectiveness of online tahsin learning in improving Qur’anic reading skills among older adults and to examine its contribution to spiritual and psychological well-being. A qualitative approach with a literature-based evaluative design was employed using the CIPP evaluation model (Context, Input, Process, and Product). Data were collected from relevant scholarly articles, previous studies, program documents, and supporting literature related to tahsin learning, Islamic education, and elderly education. The findings indicate that online tahsin programs provide flexible and accessible learning opportunities for older adults while fostering continuous religious engagement. The implementation of talaqqi and talqin methods through digital platforms contributes positively to improving tajwid accuracy, makharijul huruf, learning motivation, and emotional well-being among elderly participants. However, several challenges remain, including limited digital literacy, declining memory capacity, and the need for intensive mentoring and adaptive instructional strategies. The study concludes that online tahsin programs represent an important innovation in sustainable Islamic education for elderly communities and recommends the development of more inclusive, andragogical, and technology-assisted learning models to support lifelong Qur’anic education.